2023
DOI: 10.1371/journal.pgen.1010522
|View full text |Cite
|
Sign up to set email alerts
|

Functional impact of subunit composition and compensation on Drosophila melanogaster nicotinic receptors–targets of neonicotinoids

Abstract: Neonicotinoid insecticides target insect nicotinic acetylcholine receptors (nAChRs) and their adverse effects on non-target insects are of serious concern. We recently found that cofactor TMX3 enables robust functional expression of insect nAChRs in Xenopus laevis oocytes and showed that neonicotinoids (imidacloprid, thiacloprid, and clothianidin) exhibited agonist actions on some nAChRs of the fruit fly (Drosophila melanogaster), honeybee (Apis mellifera) and bumblebee (Bombus terrestris) with more potent act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Thus, this compensation mechanism could only take place in dsRNA‐ β 2‐treated adults because the level of expression of the β 2 subunit has reached a low threshold, whereas the dsRNA‐ β 2‐treated larvae still have a high enough expression level of this subunit to avoid triggering such a mechanism. Moreover, such a compensation mechanism has also been reported in the Colorado beetle Leptinotarsa decemlineata treated with dsRNAs targeting the Ldα1 subunit 28 and in the fruit fly Drosophila melanogaster treated with dsRNAs targeting either Dα1, Dα2 or Dα3 29 . However, in these cases, no induced mortality has been reported after RNAi treatment.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Thus, this compensation mechanism could only take place in dsRNA‐ β 2‐treated adults because the level of expression of the β 2 subunit has reached a low threshold, whereas the dsRNA‐ β 2‐treated larvae still have a high enough expression level of this subunit to avoid triggering such a mechanism. Moreover, such a compensation mechanism has also been reported in the Colorado beetle Leptinotarsa decemlineata treated with dsRNAs targeting the Ldα1 subunit 28 and in the fruit fly Drosophila melanogaster treated with dsRNAs targeting either Dα1, Dα2 or Dα3 29 . However, in these cases, no induced mortality has been reported after RNAi treatment.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, such a compensation mechanism has also been reported in the Colorado beetle Leptinotarsa decemlineata treated with dsRNAs targeting the Ld⊍1 subunit 28 and in the fruit fly Drosophila melanogaster treated with dsRNAs targeting either D⊍1, D⊍2 or D⊍3. 29 However, in these cases, no induced mortality has been reported after RNAi treatment.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…laevis oocytes, which represent the first instance of recombination with the α and β subunits of agricultural pests (thrips). Previous studies have shown that altering injection ratios or coinjecting with α3, α4, and β3 can lead to the formation of nAChRs with distinct functions. , However, it is worth noting that neonicotinoids are predicted to target the α1, α2, β1, and β2 subunits of insect nAChRs . Therefore, the homozygous expression of these receptors can serve as a valuable screening tool for the discovery of novel insecticidal compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The nAChRs are ligand-gated cation channels, conserved among insects that, once activated, lead to calcium ion (Ca 2+ ), sodium ion (Na + ), or potassium ion (K + ) flux into neurons, regulating a range of neuromotor and behavioural responses. 8 Imidacloprid targets subunits nAChR⊍1, nAChR⊍2, nAChR⊍3, nAChR⊍4, nAChR⊎1, nAChR⊎2 and nAChR⊎3, [9][10][11] whilst spinosad targets nAChR⊍6. 12,13 An imidacloprid dose of 2.5 ppm creates a long-lasting low Ca 2+ flux into neurons expressing nAChRs, further reducing their cholinergic response by more than two-fold.…”
Section: Introductionmentioning
confidence: 99%